PENGGUNAAN SURAT KETERANGAN DOMISILI DALAM PENGATURAN HUKUM KEPEMILIKAN TANAH ABSENTE BERKAITAN DENGAN PRAKTEK JUAL-BELI TANAH DI WILAYAH KANTOR TANAH KABUPATEN GROBOGAN - Danang Prasetya Nugraha; Jawade Hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The use of the Certificate of Domicile in the process of sale of Agricultural Land Sale, can be negative in the absence of land ownership of agricultural land whose owner is located outside the subdistrict area of the land where the writer wishes to study more in whether in the implementation of the use of the certificate of domicile has been in accordance with the provisions of its enforcement, so the author formulated some of the first issues in how the use of a certificate of domicile in terms of sale of agricultural land if the buyer is domiciled outside the subdistrict of the purchased agricultural land, the second is how the legal consequence of the use of Domicile Certificate in the absence of sale of agricultural land.In the approach the writer uses is a juridical-empirical approach. the juridical approach is used to analyze the rules related to Domicile Litigation in the legal arrangement of Absente Land Ownership in relation to the practice of sale and purchase at the Land Office of Grobogan Regency, while the empirical approach used to analyze the existing law is seen as the behavior of people patterned on the life of society who always interact and deal with social aspects.In the result of the research on the first problem it can be concluded that in the implementation of sale of agricultural land (absente) by using domicile certificate that is not in accordance with ID card is not allowed in the rule of law which is in effect as opposed to Article 10 of Agrarian Basic Law year 1960, so the use of the certificate of domicile should correspond to the original domicile, and is understood to be the real settlement for settlement, while the second problem can be drawn to the conclusion that the legal consequences in the use of a domicile certificate that does not correspond to the original residence in the case of sale buy agricultural land, making the transfer of the right to the land office becomes ineffective because it does not comply with the administrative requirements of national regulation No. 1 of 2010, as well as transfers of agricultural land purchase rights using non-compliant landlords t the real can be null and void. Keywords: Domicile, Selling, Absentee Certificate